SERVET-İ FÜNÛN DERGİSİNDEKİ İKTİSADA İLİŞKİN MAKALE VE YAZILARIN AÇIKLAMALI BİBLİYOGRAFYASI (1891-1928) - (:unkn) unknown (My University, 2017)
Kuruluşundan bu yana altı asırdır yaşanmayan ve neredeyse her alandaki top yekûn değişim, Osmanlı'da 19. yüzyılda görülmeye başlanır. Mısır'ın tahliyesi, Sened-i ittifak, Yeniçeriliğin kaldırılması, yeni bir ordunun kurulması, Balkan isyanları, Tanzimat'ın ilanı, gazete ve dergi yayıncılığı, mühendislik ve tıp gibi pek çok alanda yeni okulların açılması, Islahat Fermanı ve I. Meşrutiyet'in ilanı gibi pek çok yenilik bu yüzyılda yaşandı. Söz konusu dönemdeki gazete ve dergi yayıncılığının geç örneklerinden biri de Servet-i Fünûn dergisidir. I. Meşrutiyet'te Recaizade Mahmud Ekrem'in Mekteb-i Mülkiye'den öğrencisi Ahmet İhsan Tokgöz tarafından çıkarılmaya başlanan dergi, Cumhuriyet döneminde de yayın hayatını sürdürür. Dergide kimi zaman bilimsel yazılar, kimi zaman edebi yazılar ön plana çıkar. Edebiyatta bir akım yaratan dergi, diğer alanlarda bu etkiyi yapamamıştır. Edebiyat dergisi olarak bilinen Servet-i Fünûn, sadece edebiyat konularının ele alındığı bir dergi değildir. Bilimsel gelişmelere ilişkin yazıların da yer aldığı dergide iktisat, felsefe, psikoloji, sağlık, sosyoloji, basın, teknoloji, eğitim, müzik, kimya ve şehir gibi konulardaki makale, yazı, haber, resim, ilan ve reklamlara yer verilmiştir. Dergi, salt iktisat yazılarının dışında, iktisadın alt dalları altında sayılabilecek maliye, ticaret, hayvancılık, ziraat, ulaşım, işletme, enerji-maden ve şehircilik gibi alanlardaki yazılara da yer vermiştir. Burada yapılan çalışma, dergideki, iktisadın alt dallarını değil, salt iktisat alanındaki Osmanlıca makale ve yazıların açıklamalı biyografisini sunmaktan ibarettir

In the 19th century, a total change almost in the every area of the Ottoman Empire which had not be ever seen for six century since its foundation had came to be experienced. In this century took place many innovations such as Egyptian evacuation, Sened-i alliance, removal of the Janissaire, the establishment of a new army, Balkan rebellions, the Tanzimat's declaration, newspaper and magazine publishing, opening of new schools in many areas such as engineering and medicine, the Islahat Fermanı and the First Constitutionnalisme. The magazine Servet-i Funun is one of the late examples of the newspaper and magazine publishing in this period. The magazine which was started to published by Ahmet Ihsan Tokgoz who was Recaizade Mahmoud Ekrem's student from Mekteb-i Mulkiye, had also continued his publishing life in the Republican period. Sometimes scientific writings and sometimes literary writings had been at the forefront in the magazine. The magazine which created a trend in literature could not make this effect in other fields. The magazine known as the literary magazine is not a magazine dealing only with literary subjects. In the magazine containing articles related to scientific developments is also included articles, essays, news, pictures, announcements and advertisements in the areas like economics, philosophy, psychology, health, sociology, press, technology, education, music, chemistry, city too. Besides the purely economic articles, this magazine also contains articles in such areas as finance, commerce, stockbreeding, agriculture, transportation, business, energy-mining and urbanism that can be counted under the lower branches of economics. The study being carried out here presents not only subdivisions of economics, but also explanatory biography of Ottoman articles and writings in the field of economics
AN EXPLAINED BIBLIOGRAPHY OF ARTICLE AND WRITINGS RELATED TO ECONOMICS IN THE MAGAZINE SERVET-I FÜNUN (1891-1928)